Sistem Pemantauan Parkir Liar Menggunakan Sensor Infrared Berbasis Android (Studi Kasus Politeknik Negeri Malang) - Nur Ahmad Wasian; Mila Kusumawardani; Ridho Hendra Yoga Perdana (Jurnal Jaringan Telekomunikasi, 2021)
Illegal parking in Malang State Polytechnic is still not well monitored. The Officer Pengamanan Dalam(Pamdal), whose job is to curb Polinema residents who park their vehicles, cannot monitor the vehicles regularly, so there are still many who park illegally. Based on this, an automatic system that can be used by Pamdal to monitor illegal parking in Polinema is needed. Therefore, "Illegal Parking Monitoring Information System Using Infrared Sensor Based On Android" was created. The system built uses several components, including Arduino Nano, ESP32 Cam, Infrared Sensor, and servo motor. With the making of this tool and research, it is hoped that it will be able to assist in disciplining polynemaic residents to order parking through monitoring of the system being built. Three pieces of equipment were made and placed in front of the AH Building, in front of the AI ??Building, and next to the AO Building. The results of the experiment for notifications from the three nodes have different delays in sending data from the node to the smartphone on the user side. Delay at node two has the greatest delay, which is 193.0708 ms. Meanwhile, node three has excellent performance with an average delay value of 107.0723 ms.